Modern weapons and military equipment for issue 3/2013 - Vučković, Dragan M (Vojnotehnički glasnik / Military Technical Courier, 2013)
Why extinguishes the Global Hawk Block 40 program; Turkey seeks an amendment to a fifth-generation fighter for JSF; Northrop is fighting for its Global Hawk flies while Triton departs; Su-35 in the center of attention in Paris; Stop and ejected; Quick blow with a hammer; The allegations in the terminal stage; Purchase of Russian weapons continues.